Disorders induced by chromium to health and the use of antioxidants in the prevention or treatment - Sergio L. Becerra-Torres; César Soria-Fregozo; Fernando Jaramillo-Juárez; José L. Moreno-Her (GarVal Editorial Ltda., 2014)
The cell maintains a constant balance of redox processes, thus preserving regulating the balance between pro-oxidant production and antioxidant defense systems. Disruption of this balance leads to oxidative stress state which is characterized by increased levels of free radicals, leading to damage or cell death. Oxidative stress is associated with the pathogenesis of various diseases. In this regard, the evidence shows the oxidizing capacity of heavy metals, including chromium. However, this event can be regulated by nucleophilic nature substances which prevent or reverse the respective disorders. In this context, when the capacity of cellular response against the action of reactive oxygen species is suppressed, the intake of products that help keep the respective functional integrity is indispensable. Already reported some beneficial effects of antioxidants on the functional alterations promoted by heavy metals. The intent of this review is to summarize the scientific ability of chromium to induce pathology in different organ systems and the ability of some antioxidants to prevent or reverse this quality.